Nearshore Bathymetry Estimation Using Video Coastal Monitoring System - Zikra, Muhammad (IPTEK The Journal for Technology and Science, 2008)
The invention of new digital technology of images from video camera systems now can provide information of the shoreward propagation of wave using pixel intensity time series that collected at cross-shore array. From this video image of intensity data, we can measure the wave speed (or, equivalent to wave number). Then the local water depth is inferred from linear wave theory dispersion relation equation. This paper describes the cross-spectral correlation approach scheme for investigating wave speed or equivalent wave number from video image data sets. The approach based on a pixel array analysis that utilizes a nonlinear inverse method. The solution is tolerant to noise and other forms of sampling deficiency. The solution includes error predictions that can be used to evaluate sample designs (data gaps) and the signal coherence. The technique was tested using 30 days of hourly data collected at Egmond beach, Netherlands. The result showed that the method have capability to derive wave number prediction from pixel intensity time series to support bathymetry estimation in near shore area through inversion of an appropriate wave dispersion model.